Keseimbangan Pasar dan Peran Negara Dalam Sistem Ekonomi Islam Menurut Alquran dan Hadits - Malik Akbar, Nanang; Kustiawati, Dedek; Cilabanyu Vivi Hartono, Ning; Azzahra Sena, Luthfiana (Jurnal Etnik: Ekonomi-Teknik, 2023)
Market equilibrium is a price agreement that occurs in a market system between sellers and buyers with a mechanism of bargaining. The presence of demand and supply encourages a bargaining process aimed at obtaining a balanced price. The market can be said to get a price balance when the asking price matches the bid price. The process of demand and supply is also in the perspective of Islamic economics. The research method used in this research is library research or literature research. The results of the study show that in Islamic economics there are conditions related to the Al-Qur'an and Hadith, namely the concept of a good economy and in accordance with Islamic teachings. The view of Islamic teachings regarding market balance is relatively the same but has certain limitations with the aim of fulfilling Islamic principles.